Securing Blockchain Networks like Ethereum and Hyperledger Fabric : Learn advanced security configurations and design principles to safeguard Blockchain networks /: Learn advanced security configurations and design principles to safeguard Blockchain networks. (2020) - Parisi, Alessandro
No abstract available